ปัญหาเกี่ยวกับการคุ้มครองข้อมูลส่วนบุคคล ของผู้เข้ารับการรักษาพยาบาล - ยุติธรรม วิภาวดี (Academic Journal Phranakhon Rajabhat University, 2015)
การวิจัยในครั้งนี้มีวัตถุประสงค์ เพื่อศึกษา ปัญหาที่เกี่ยวกับการคุ้มครองข้อมูลส่วนบุคคลของผู้ เข้ารับการรักษาพยาบาล อันมีผลมาจากการพัฒนาของ เทคโนโลยีสารสนเทศและการสื่อสาร โดยมีกฎหมายที่ ประกาศใช้เกี่ยวกับการคุ้มครองข้อมูลส่วนบุคคลของ ผู้เข้ารับการรักษาพยาบาลอยู่หลายฉบับ ซึ่งกฎหมาย ดังกล่าวให้ความคุ้มครองข้อมูลส่วนบุคคลโดยทั่วไป รวมทั้งข้อมูลส่วนบุคคลของผู้เข้ารับการรักษาพยาบาล ข้อมูลประวัติสุขภาพ คือข้อมูลสุขภาพของบุคคล เป็นความลับส่วนบุคคล การเปิดเผยข้อมูลแก่ผู้ที่ไม่ เกี่ยวข้องกับการรักษาพยาบาลไม่อาจทำได้ เว้นแต่จะ ได้รับความยินยอมจากเจ้าของข้อมูล หรือมีกฎหมาย กำหนดให้เปิดเผยข้อมูลได้ การเข้ารับการรักษาพยาบาล ของผู้ป่วยแต่ละคนจะมีการบันทึกประวัติไว้ในเวช ระเบียน ซึ่งข้อมูลในเวชระเบียนของผู้ป่วยที่เข้ารับ การรักษา ถือเป็นข้อมูลส่วนบุคคลด้านสุขภาพที่เป็น ความลับของผู้เข้ารับการรักษาพยาบาล การคุ้มครอง ข้อมูลส่วนบุคคลดังกล่าวได้มีบทบัญญัติของกฎหมาย ประกาศใช้เพื่อให้ความคุ้มครองข้อมูลส่วนบุคคล เพื่อ มิให้ผู้ครอบครองข้อมูลเปิดเผยข้อมูลแก่บุคคลอื่น เว้น แต่จะได้รับความยินยอมจากเจ้าของข้อมูล สิทธิที่จะ ได้รับความคุ้มครองข้อมูลส่วนบุคคลเป็นสิทธิส่วน ตัวอันเป็นสิทธิขั้นพื้นฐานหรือสิทธิตามธรรมชาติของ มนุษย์ ซึ่งประเทศไทยได้บัญญัติไว้ในรัฐธรรมนูญแห่ง ราชอาณาจักรไทย พ.ศ.2550 มาตรา 35 ข้อมูลของผู้ป่วยจะมีการจัดเก็บไว้ในเวช ระเบียน กฎหมายห้ามผู้ครอบครองข้อมูลส่วนบุคคล ของผู้ป่วยเปิดเผยข้อมูล แต่มีข้อยกเว้นให้เปิดเผยได้ ในบางกรณีหากการเปิดเผยนั้นเป็นประโยชน์ต่อส่วน รวม หรือหากได้รับความยินยอมจากเจ้าของข้อมูล และจากคำประกาศสิทธิของผู้ป่วย ผู้ป่วยมีสิทธิได้รับ การปกปิดข้อมูลเกี่ยวกับตนเอง จากผู้ประกอบวิชาชีพ ด้านสุขภาพโดยเคร่งครัด เว้นแต่ได้รับความยินยอมจาก ผู้ป่วยหรือการปฏิบัติหน้าที่ตามกฎหมาย จากการศึกษาแนวคิดและทฤษฎีเกี่ยวกับ การคุ้มครองข้อมูลส่วนบุคคลของผู้เข้ารับการรักษา พยาบาลนั้น พบว่าแม้จะมีกฎหมายบัญญัติให้ความ คุ้มครองข้อมูลส่วนบุคคลของผู้เข้ารักษาพยาบาลก็ตาม แต่มีหลักการหรือแนวทางในการที่จะเปิดเผยข้อมูล ส่วนบุคคลได้หลายทาง เช่น ใช้หลักความเหมาะสม (Principle of Suitability) หลักความจำเป็น (Principle of Necessity) หลักความสมดุล (Principle of Proportionality Stricto Sensu หรือ Theorie du bilan) หลักความยินยอม (Volenti non fit injuria) และหลักเพื่อประโยชน์สาธารณะ Problems Relating to the Protection of Personal Data in the Medical Treatment of Patients This thesis aims to study problems concerning protection of patients’ personal information due to information technology and communication development. There are many laws concerning protection of patients’ personal information. Such laws provide privacy protection in general, including patients’ information. Health information is a person’s health information which is personally confidential. It is impermissible to disclose information to other persons not related to medical treatment unless receiving information owner’s consent or it is otherwise specified by law Each patient’s admission to hospital is recorded in a medical record which is considered as health personal information. It is also confidential. Protection of patient’s personal information is provided by law in order to protect personal information and to prohibit persons obtaining such information to disclose such information to others unless obtaining information owner’s consent. The rights to be protected on personal information is personal rights as well as basic rights. It is human’s natural right. Thailand recognizes the rights in Section 35, the Constitution of The Kingdom of Thailand, B.E. 2550 (2007). Patients’ information is recorded in medical records. The law prohibits information holders to disclose information. There are some exceptions however. For example, such disclosure is for the benefit of public or an information owner allows such disclosure. According to the Declaration of Patient’s Rights, patients have the rights to expect that their personal information is strictly kept confidential by the medical practitioner unless obtaining a patient’s consent or due to legal obligation. From the study about concept and theory on protection of patients’ personal information, even though there are laws providing protection of patients’ personal information, there are various principles concerning disclosing personal information such as principle of suitability, principle of necessity, principle of proportionality Stricto Sensu or Theorie du bilan, Volenti non fit injuria principle and principle of public interest.